2020
DOI: 10.1155/2020/7523914
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Ratio of Blood CD56bright NK to CD56dim NK Is a Distinguishing Feature of Primary Sjögren’s Syndrome

Abstract: Objective. The aim of this study was to characterize the subsets of circulating CD56+ NK cells in pSS patients and their potential value in the diagnosis and/or prediction of prognosis in patients with pSS. Methods. We included 52 pSS patients fulfilling the 2002 AECG criteria or 2012 ACR criteria and 20 age- and gender-matched healthy volunteers. The frequency and absolute number of NK cells and CD56 NK cell subsets in peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The main reason for the marked CD4 + T-cell lymphopenia in different age-onset pSS patients needs to be further studied. Interestingly, we also found CD16/CD56+ NK cells, innate lymphoid cells that exhibit a potential regulatory role in exocrine gland tissues and the peripheral blood of pSS disease [ 17 , 18 ] were significantly decreased in the early-onset group. Our data provide evidence that the immunological status may contribute to the distinct features of different age-onset pSS patients.…”
Section: Discussionmentioning
confidence: 72%
“…The main reason for the marked CD4 + T-cell lymphopenia in different age-onset pSS patients needs to be further studied. Interestingly, we also found CD16/CD56+ NK cells, innate lymphoid cells that exhibit a potential regulatory role in exocrine gland tissues and the peripheral blood of pSS disease [ 17 , 18 ] were significantly decreased in the early-onset group. Our data provide evidence that the immunological status may contribute to the distinct features of different age-onset pSS patients.…”
Section: Discussionmentioning
confidence: 72%
“…The relative and total numbers of circulating NK cells and CD56 dim NK cells were lower while the number of CD56 bright NK cells was higher in pSS patients compared to healthy control subjects (67,68). The ratio of CD56 bright to CD56 dim NK cells was correlated with IgG level and showed diagnostic utility for pSS with good sensitivity and specificity (67). The lower numbers of circulating NK cells and CD56 dim NK cells in pSS patients may lead to their infiltration into glands and focal immune injury.…”
Section: Nk Cells and Sjögren's Syndromementioning
confidence: 79%
“…However, recent findings have suggested that innate immunity-especially NK cells-plays a role in SS pathogenesis (64)(65)(66). The relative and total numbers of circulating NK cells and CD56 dim NK cells were lower while the number of CD56 bright NK cells was higher in pSS patients compared to healthy control subjects (67,68). The ratio of CD56 bright to CD56 dim NK cells was correlated with IgG level and showed diagnostic utility for pSS with good sensitivity and specificity (67).…”
Section: Nk Cells and Sjögren's Syndromementioning
confidence: 99%
“…We noted a weak negative correlation between the IFN score and the fraction of NK cells. The role of NK cells in pSS pathogenesis is unclear, and reduced NK cell numbers and activity in pSS have been reported, as well as a shift within the NK cell sub-populations (32,33). The reasons behind the negative correlation observed is unclear and needs to be further explored.…”
Section: Discussionmentioning
confidence: 98%